Multiple Plasmid Vectors Mediate the Spread of fosA3 in Extended-Spectrum-β-Lactamase-Producing Enterobacterales Isolates from Retail Vegetables in China - Luchao Lv (American Society for Microbiology, 2020)
ABSTRACT The plasmid-mediated fosfomycin resistance gene fosA3 has been detected in Enterobacterales from various sources but has rarely been reported in vegetables. In this study, the aim was to investigate the prevalence of and, subsequently, to characterize fosA3-positive Enterobacterales isolates from retail vegetables. Seventeen (7.3%) fosA3-carrying strains were identified from 233 extended-spectrum-β-lactamase-producing Enterobacterales isolates from vegetables. All 17 isolates, including six Escherichia coli, seven Klebsiella pneumoniae, two Raoultella ornithinolytica, and two Citrobacter freundii isolates, carried blaCTX-M. S1-nuclease pulsed-field gel electrophoresis (S1-PFGE) and hybridization confirmed that the fosA3 genes in 16 isolates were located on plasmids ranging in size from ∼40 kb to ∼250 kb, except one located on chromosome of C. freundii. All the fosA3-carrying plasmids from 16 fosA3-positive isolates were successfully transferred into the recipient bacteria by transformation or conjugation. In agreement with data determined with isolates from food animals, the IncHI2/ST3 and IncN-F33:A-:B-/F33:A-:B plasmids were the main vectors of fosA3 in E. coli. Additionally, F24:A-:B1, IncFIIK-IncR, IncFIIS, IncR, and two untypeable plasmids were found for the first time to be vectors for fosA3 in Enterobacterales. The genetic contexts of fosA3 in 15 Enterobacterales isolates differed due to insertion and/or loss of molecular modules mediated by mobile elements. However, all fosA3 genes were flanked by IS26, as commonly observed in other fosA3-carrying plasmids. Here, we report a high rate of detection of fosA3 genes, mediated by multiple plasmid vectors, in ESBL-producing Enterobacterales from retail vegetables. FosA3-producing Enterobacterales could be transmitted to the human body by direct contact or consumption of vegetables, which might pose a potential threat to public health. IMPORTANCE This report provides important information on the transmission and epidemiology of fosA3 among Enterobacterales isolates from vegetables. The rate of occurrence of fosA3 in ESBL-producing Enterobacterales from retail vegetables is high, and fosA3 was found to be carried by diverse plasmids. Some novel genetic contexts of fosA3 and novel fosA3-carrying plasmids, including several plasmid types common in K. pneumoniae, were identified, increasing the number of known transfer vectors for the fosA3 gene and reflecting the complexity of fosA3 transmission in Enterobacterales. The capture of fosA3 by the resident plasmid of K. pneumoniae will accelerate the spread of fosA3 in K. pneumoniae, one of the most pathogenic species in clinical medicine. Considering the clinical importance of fosfomycin, and the fact that vegetables are directly consumed, the fosfomycin resistance genes present a risk of transmission to the human body through the food chain and thus pose a threat to public health.